Late Quaternary strike-slip along the Taohuala Shan-Ayouqi fault zone and its tectonic implications in the Hexi Corridor and the southern Gobi Alashan, China - Yu, J; Zheng, W; Zhang, P; Lei, Q; Wang, X; Wang, W; Li, X; Zhang, N (Elsevier, 2017)
The Hexi Corridor and the southern Gobi Alashan are composed of discontinuous a set of active faults with various strikes and slip motions that are located to the north of the northern Tibetan Plateau. Despite growing understanding of the geometry and kinematics of these active faults, the late Quaternary deformation pattern in the Hexi Corridor and the southern Gobi Alashan remains controversial. The active E-W trending Taohuala Shan-Ayouqi fault zone is located in the southern Gobi Alashan. Study of the geometry and nature of slip along this fault zone holds crucial value for better understanding the regional deformation pattern. Field investigations combined with high-resolution imagery show that the Taohuala Shan fault and the E-W trending faults within the Ayouqi fault zone (F2 and F5) are left-lateral strike-slip faults, whereas the NW or WNW-trending faults within the Ayouqi fault zone (F1 and F3) are reverse faults. We collected Optically Stimulated Luminescence (OSL) and cosmogenic exposure age dating samples from offset alluvial fan surfaces, and estimated a vertical slip rate of 0.1–0.3 mm/yr, and a strike-slip rate of 0.14–0.93 mm/yr for the Taohuala Shan fault. Strata revealed in a trench excavated across the major fault (F5) in the Ayouqi fault zone and OSL dating results indicate that the most recent earthquake occurred between ca. 11.05 ± 0.52 ka and ca. 4.06 ± 0.29 ka. The geometry and kinematics of the Taohuala Shan-Ayouqi fault zone enable us to build a deformation pattern for the entire Hexi Corridor and the southern Gobi Alashan, which suggest that this region experiences northeastward oblique extrusion of the northern Tibetan Plateau. These left-lateral strike-slip faults in the region are driven by oblique compression but not associated with the northeastward extension of the Altyn Tagh fault.